1956
DOI: 10.1172/jci103326
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Variations in Solute Excretion and Glomerular Filtration on Water Diuresis 1

Abstract: A sustained positive load of water administered to a normal subject results in maximal water diuresis associated with a minimal concentration of solutes in the urine. The term "physiological diabetes insipidus" has been applied to this situation, because under these circumstances, the release of antidiuretic hormone from the posterior pituitary is inhibited and as a consequence, that part of the water of glomerular filtrate that is normally reabsorbed under the influence of this hormone is excreted. During sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1957
1957
1992
1992

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 11 publications
3
25
0
Order By: Relevance
“…In other terms, the presence of solute in tubule urine decreases the activity of water and thereby its rate of outward diffusion. 4 The results of a number of other studies (13,14) as well as those reported here in dogs during ADH suppression are consistent with this view. In the presence of large amounts of vasopressin, on the other hand, permeability may be sufficient to permit equilibration of water on both sides of the tubule membrane despite the opposing influence of intratubular solute.…”
Section: Discussionsupporting
confidence: 87%
“…In other terms, the presence of solute in tubule urine decreases the activity of water and thereby its rate of outward diffusion. 4 The results of a number of other studies (13,14) as well as those reported here in dogs during ADH suppression are consistent with this view. In the presence of large amounts of vasopressin, on the other hand, permeability may be sufficient to permit equilibration of water on both sides of the tubule membrane despite the opposing influence of intratubular solute.…”
Section: Discussionsupporting
confidence: 87%
“…The findings suggest that the defective water diuresis is not due to a continued nonosmotic stimulus for ADH release but do not, however, entirely obviate that possibility (10,(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 70%
“…Control collections were begun approximately 45 minutes after a priming dose and constant sustaining infusion of inulin had been started. Analysis of plasma and urine for sodium, potassium, inulin, creatinine, and osmolality were made by methods previously reported (1,10).…”
mentioning
confidence: 99%
“…Such an increase in urinary solute is known to augment the diuresis resulting from administration of large water loads (14,15,(19)(20)(21)(22). Moreover, when the magnitude of diuresis in water-loaded subjects is enhanced by increasing the solute load, the concentration of total solute characteristically rises (22,23). On the other hand the rise in solute output during steroid administration, when it occurred, was so small compared to the increase in urine flow that solute concentration fell.…”
Section: Fig 3 Changes In Glomerular Filtration Rate (Cin) During Hmentioning
confidence: 99%